Effects of vitamin C and vitamin E on performance, digestion of nutrients and carcass characteristics of Japanese quails reared under chronic heat stress (34 °C) - Şahin, Kazım; Küçük, Ömer (Wiley, 2001)
This study was conducted to determine the effects of vitamin C (L-ascorbic acid) and vitamin E (DL-alpha -Tocopheryl acetate) on performance, digestion of nutrients and carcass characteristics of Japanese quails reared under chronic heat stress (34 degreesC). A total of 180 10-day-old Japanese quails were randomly assigned to six treatment groups, three replicates of 10 birds each. The birds with a 2 X 3 factorial design received either two levels of vitamin C (100 and 200 mg/kg of diet) or three levels of vitamin E (125, 250, or 500 mg/kg of diet). Then, 200-mg vitamin C/kg of diet, compared with that of 100 mg/kg of diet, and higher dietary vitamin E inclusions resulted in a higher performance. The interaction between vitamin C and vitamin E for final body weight change (p = 0.01) and feed efficiency (p = 0.02) was detected. Final body weight change and feed efficiency increased to a higher extent by increasing dietary vitamin C when higher vitamin E levels were fed. Carcass characteristics improved with an increase of both dietary vitamin C and vitamin E (p = 0.004). The interactions on carcass characteristics were all significant (p = 0.02) and manifested themselves in a way that they were improved to a higher extent by an increase of dietary vitamin C when higher vitamin E levels were fed. Digestibility of nutrients (DM, OM, CP and EE) was greater with higher dietary vitamin C (p < 0.02) and also with higher vitamin E (p = 0.07). There were no interactions detected for digestibility of nutrients (p = 0.32). Taken together, the results of the present study conclude that a combination of 200 mg of vitamin C and 250 mg of vitamin E provides the greatest performance in Japanese quails reared under heat stress and can be considered as a protective management practice in poultry diet, alleviating the negative effects of heat stress.
Keywords: Supplemental Ascorbic-Acid; Egg-Production; Laying Hens; Temperature